RETRACTED: Immersive technologies as a tool for increasing sustainability and environmental friendliness of tourism activities - Podolskaya Tatiana; Kalenova Saulesh; Vasyuta Eugenia; Bryukhanova Natalia; Ushakov Denis (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001